Environmental, social, and governance tools and investment fund portfolio characteristics: a practical-question-oriented review - Gao, Xiang; Koedijk, Kees; Ryu, Sunghan; Wetzels, Stan; Zhou, Zhenfei (Frontiers in Sustainability, 2024)
This paper presents a literature review with the aim of facilitating investment funds to understand the practical question of whether investing responsibly can make a fund's portfolios more sustainable without compromising their return/risk profiles. The study contains most of the leading ESG research from the past two decades. We conclude from this research that the relationship between ESG and return/risk profile is predominantly neutral or even positive. Many scholars have found evidence on the performance of stocks, bonds, and real estate. The findings apply to Environmental, Social, and Governance criteria separately and in different regions. We contribute to the body of knowledge accessible to ESG-asset-seeking funds by complementing the impact investment theory and by linking ESG investment to portfolio-level characteristics and investor preferences. Looking into the future, we identify recent trends and developments in this niche field of ESG at the end of the paper.